Factors affecting oral health of pregnant women: A scoping review - Zahra PoorAskari; , Hossein Hessari; Reza Yazdani (Tehran University of Medical Sciences, 2021)
Background and Aims: Pregnancy is a period with hormonal and psychological changes affecting women's oral health. The aim of present review study was to evaluate, elaborate and categorize factors affecting oral health status of pregnant women. Materials and Methods: A literature search with the following keywords: pregnancy, "pregnant women", "pregnant mothers" and "expectant mothers" , AND dentistry, "dental health" and "oral health" in PubMed and Scopus was performed from 2009 to 2019. Search results included 1435 articles which 467 duplicate studies were excluded. Finally, 30 articles were included in the study. Oral health outcomes were categorized and significant relationships with determinants and risk factors were reported. Results: Most studies (70%) were performed cross-sectionally. Among the studied outcomes, dental visit, periodontal disease and dental caries were the most common. The most studied independent variables were socioeconomic factors and demographic factors, followed by behavioral and enabling factors. The lowest frequency was related to the systemic factors. Mothers' education and age were examined more than other variables and in about 40% of studies had significant association with outcomes. Dental counseling was assessed in only 3 studies and in all three studies, the relationship with outcome was significant. Conclusion: Socioeconomic, demographic and enabling factors could affect the oral health of pregnant women.